Pemberdayaan Kader Bina Keluarga Balita Dalam Pencegahan Stunting Dan Akselerasi Taraf Ekonomi Di Desa Bresela, Kecamatan Payangan Gianyar - Luh Gede Pradnyawati; Krisna Adwitya Sanjaya (Denpasar Institute, 2020)
Stunting is a form of nutritional disorders which is characterized by a short body condition that exceeds the deficit of -2SD below WHO standards. The incidence of stunting in children under five requires special attention because it is associated with a risk of decreased intellectual ability, productivity and an increased risk of degenerative diseases in the future. Indonesia is included in a group of developing countries with a high prevalence rate, one of which is Bresela Village, Gianyar Regency. From interviews with cadres, there were several problems related to stunting prevention programs, namely the minimum information obtained by cadres and the low cadre knowledge about stunting prevention. In addition, the cadres, who are mostly craftsmen, have difficulties in marketing their merchandise, which affects their income. The partner empowered here is the BKB cadre (Toddler Family Development). Cadre empowerment is very much needed to prevent stunting in Payangan District. In general, this program can be said to be successful because there is a decrease in stunting and marketing numbers that are appropriate with technology-based in Bresela Village. The cadres re expected can spearhead the sustainability of the stunting prevention program in a sustainable manner in their respective regions so that it can empower cadres to reduce stunting problems in Gianyar Regency